The Great Silk Road: Formation, Stages of Development and Present Time (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
Abstract: In this article, the territory of Uzbekistan is located in the center of the system of ancient civilizations and mutual relations. Due to this geographical location, the interaction of cultures has increased here. Large-scale trade processes took place along the Great Silk Road, diplomatic agreements and various alliances were concluded. The Great Silk Road was not only a trade-caravan route, but left an indelible mark on the history of the civilization of Eurasian peoples.